ANALISIS POTENSI PAD PROVINSI SUMATERA SELATAN - Endang Kusdiah Ningsih; Dwi Eka Novianty (COMPETITIVE, 2020)
Optimizing management of regional economic potential is an effort to increase Own-Source Revenue (PAD) as a form of building regional financial independence so that it can reduce fiscal dependence on the central government. This study analyzes each component of PAD that can contribute to increasing PAD by using Klassen Typology. This Klassen Typology Analysis is conducted to find out the types of PAD components that fall into the advanced, advanced, depressed, potential or backward categories. The data used in this study are secondary data in the form of South Sumatra Province PAD data as an analysis area and national PAD as a reference area. The data analyzed are data from 2014-2018. The results showed that local taxes are in quadrant I of the Klassen Typology, a quadrant which explains that local taxes are a component of advanced and rapid PAD with the largest contribution of 93.53%.Furthermore, the other components of PAD, namely regional retribution, the results of the management of regional wealth and other legitimate PAD, are in quadrant III. This quadrant explains that the component of PAD is potential or can still be developed again. These results explain that the government of South Sumatra Province to further improve the management of regional user fees, the results of the management of regional wealth and other PAD in order to finance development using their own funds.